SYNTHESIS, ANTIMICROBIAL AND DOCKING STUDIES OF NOVEL BENZOTRIAZOLE DERIVATIVES - PRAMOD B. KUMAR; SUVARNA G. KINI; MUHAMMAD MUBEEN (International Journal of Pharma and Bio Sciences, 2014)
In view of the biological and clinical importance of Benzotriazole compounds, some new derivatives were synthesized and characterized on the basis of analytical and spectral data. All the new compounds were evaluated at 500µg/ml, 250µg/ml and 100µg/ml for the antibacterial and antifungal activity. Some of the compounds showed moderate to good antimicrobial activity against gram positive and gram negative bacteria. Compound BT1 was found to be of potent activity against Candida albicans at a concentration of 500µg/ml. Docking studies of the synthesized compounds were carried out with the help of VLife MDS 4.2 software using GRIP batch docking method to validate the results obtained in in-vitro studies